Acoustic Analysis of Hoarseness - NP, Nataraja (Journal of All India Institute of Speech and Hearing)
’Hoarseness’ is a general term used by Speech Clinicians and others to describe a variety of perceived voice abnormalities. Hoarseness has been identified as a symptom of abnormal laryngeal condition. Considerable emphasis has been placed on this symptom. Several approaches, including acoustic, cinematographic, aerodynamic and electrophysiological have been utilised to explore the mechanism and pathologic physiology of hoarse voice production. However, the evaluation of hoarseness, the estimation of degree and quality of hoarseness has been made chiefly on the basis of clinicians’ subjective perception. This practice has led to the creation of confusing terms to describe similar changes of vocal quality. Terms like harsh, husky, raspy, breathy and strindent are also often used by clinicians’ hoarseness. Little is known about acoustical properties of variations of pathologic voices and related dysfunction of the larynx.